Equity in ecosystem restoration - Wells, Harry B. M.; Kirobi, Elijah H.; Chen, Cadia L.; Winowiecki, Leigh A.; Vågen, Tor‐Gunnar; Ahmad, Muhammad N.; Stringer, Lindsay C.; Dougill, Andrew J. (Restoration ecology, 2021)
The importance of equity has been emphasized in climate change, biodiversity loss, land degradation, and ecosystem restoration. However, equity implications are rarely considered explicitly in restoration projects. Although the role of equity has been studied in the context of biodiversity conservation and environmental governance, environmental variables are often ignored in equity studies, and spatial analyses of equity are lacking. To address these gaps, we use a mixed methods approach, integrating spatially explicit ecological and social data to evaluate, through an equity lens, a restoration project in a semi‐arid rangeland socioecological system in Kenya. We use questionnaires and semi‐structured key informant interviews to explore four dimensions of equity: distributional, procedural, recognitional, and contextual. Our results show that restoration employment and distance to the restoration site strongly influence perceived distributional and procedural equity. Employment and distance to restoration site can interact in counterintuitive ways in their influence on aspects of perceived equity, in this case, the fairness of site selection. Our findings exemplify that equity dimensions are intimately linked, and trade‐offs can occur between equity dimensions, across socio‐temporal scales, and in choosing the ethical framework to apply. Our work demonstrates how restoration is influenced by different dimensions of equity and we opine that incorporating equity in project planning and implementation processes can improve restoration outcomes. We emphasize the importance of respecting plurality in the values systems and ethical frameworks that underlie what is considered equitable, while negotiating trade‐offs between diverse ethical positions in the design and implementation of ecosystem restoration projects.